Majorization problems for p-valently meromorphic functions of complex order involving certain integral operator - Janani, Thambidurai; Murugusundaramoorthy, Gangadharan (Global Journal of Mathematical Analysis, 2014)
The main object of this paper is to investigate the problem of majorization of certain class of meromorphic p-valent functions of complex order involving certain integral operator. Moreover we point out some new or known consequences of our main result. Keywords: Meromorphic functions, Starlike functions, Convex functions, Majorization problems, Hadamard product (convolution), Integral operator.